Constrained optimised flexible power control for grid‐connected converters under unbalanced faults. Issue 6 (25th May 2021) - Rufa'I, Nabila Ahmed; Zhang, Li; Chong, Benjamin
Abstract: This paper presents a constrained multi‐objective optimisation scheme for a grid‐connected voltage source converter operating under unbalanced voltage conditions in a three‐phase three‐wire system. The scheme is aimed at evaluating the converter reference currents required to supply all the power generated by the connected source to the grid, whilst simultaneously suppressing oscillations of both real and reactive powers. The trade‐off between these two conflicting requirements is achieved by setting a single cost function with variable weightings. Two constraints are set to restrict the converter instantaneous phase current and maintain low DC‐bus voltage percentage ripple. A genetic algorithm is applied to search for the optimal solution. Simulation results are presented and confirm the effectiveness of the proposed method.